A Clinical Practice Guideline to Guide a System Approach to Diabetes Care in Hong Kong - Lau, Ip Tim (Diabetes Metab J, 2017)
The Hospital Authority of Hong Kong is a statutory body that manages all the public medical care institutions in Hong Kong. There are currently around 400,000 diabetic patients under its care at 17 hospitals (providing secondary care for 40%) and 73 General Outpatient Clinics (providing primary care for 60%). The patient population has been growing at 6% to 8% per year over the past 5 years, estimated to include over 95% of all diagnosed patients in Hong Kong. In order to provide equitable and a minimal level of care within resources and local system factors constraints, a Clinical Practice Guideline on the management of type 2 diabetes mellitus was drawn in 2013 to guide a system approach to providing diabetes care. There is an algorithm for the use of various hypoglycemic agents. An organizational drug formulary governs that less expansive options have to be used first. A number of clinical care and patient empowerment programs have been set up to support structured and systematic diabetes care. With such a system approach, there have been overall improvements in diabetes care with the percentage of patients with glycosylated hemoglobin <7% rising from 40% in 2010 to 52% in 2015.